Pakkebbua Batu: Studi Kerawanan Ekologi dan Kehidupan Ekonomi Masyarakat di Desa Allakuang, Kecamatan Maritengngae, Kabupaten Sidrap - zulkifli - zulkifli (Department Anthropology, Faculty of Social and Political Sciences Hasanuddin University., 2017)
The existence of mountain rock has become a grace for people in Desa Allakuan, particularly for craftsmen, and has been used by others from different part of Sidrap. This article aims to explore the craftsmen’s activities and and the impacts of such activities toward the surrounding society, particularly towards craftsmen themselves. The result shows that craftmen are hereditary work. Children are introduced and get involved in such kind of work together with their fathers since childhood. As the result, they are accustomed to such kind of work, and from one generation to another and this has impacted on their motivation to continue their study. However, their perception about being craftmen is rather ambivalent, as a grace as well as a trap since their level of education is low and they do not have other skill to make money. Therefore, they very much depend on the mountain rock as the basic materials for crafts (by combining between traditional and modern technology) and for construction. Despite the fact that this has become the main source of income, it is follow by some negative impact on the environment and public health. The former is related to the mountain rock digging using heavy equipment without considering the balance between the exploitation of natural resources and its maintenance as well as occupational health and safety (K3). The latter is associated with the dust resulted from using carving machine.